Deacidification Of Crude Palm Oil Using Solvent Extraction Integrated With Membrane Technology - Heng, Sze Lu (2022)
Massive usage of chemicals and production of palm oil mill effluent (POME) of conventional deacidification, small difference in molecular weight between triacylglycerol and free fatty acid (FFA) as well as the state of crude palm oil (CPO) as semi-solid at room temperature make the membrane technology separation process unfavorable in CPO refining process. Therefore, this study was aimed to integrate solvent extraction and membrane technology to extract FFA from CPO with the benefit of solvent recovery. Different solvents including acetone, ethanol, hexane, methanol and propanol were used to extract palmitic acid from synthetic acidified palm oil. Then, palmitic acid and ethanol in synthetic extractant were separated via either pressurization or pervaporation membrane technology using five selected commercially available membrane including three polydimethyl siloxane (PDMS) with silicone based supported solvent resistant nanofiltration (SRNF) membranes (NF010206, NF030306 and NF030705), cellulose triacetate non-woven support forward osmosis (FO) membrane (CTA-NW), and polyamide thin-film composite reverse osmosis (RO) membrane (SW30XLE). The selected membranes underwent a series of characterization studies including scanning electron microscope (SEM), hydrophobicity, flux stability and flux recovery. The effects of different pressures and vacuum conditions on permeate flux and selectivity at 25 °C were investigated. In this study, pure ethanol was found to be the most effective solvent. It successfully reduced palmitic acid up to 81.28 ± 1.01% (mean ± standard deviation) at 55 °C with a synthetic acidified palm oil to pure ethanol mass ratio of 1: 4. It was found that the addition of water did not help to improve the palmitic acid extraction and the best equilibrium constant for ethanol extraction was found at 55 °C with the greatest oil extraction capacity. Hydrophobic membrane exhibited the highest permeate flux, but low palmitic acid rejection, whereas hydrophilic membrane was not suitable for CPO refining process with low permeate flux and low palmitic acid rejection. Surprisingly, SW30XLE with hydrophilic top layer and hydrophobic separation layer demonstrated a permeate flux of 36.88 L/m²h and a rejection percentage of 100% in the pressurization membrane system, implying its potential for CPO refining process. However, the membrane pervaporation system showed a very low permeate flux (1.28 L/ m²h) in most of the selected membranes which may be unfavorable for industrial usage. Therefore, further research is required to identify solvent with higher extraction ability, and membrane with higher permeation and selectivity for the integrated solvent extraction with membrane technology as an economically and environmentally friendly CPO deacidification method, followed by solvent recovery to produce high quality edible oil.